2011
DOI: 10.1097/mbc.0b013e3283456c4e
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage at both Arg306 and Arg506 is required and sufficient for timely and efficient inactivation of factor Va by activated protein C

Abstract: Background Activated protein C (APC) inactivates membrane-bound factor Va following cleavages of the heavy chain at Arg306, Arg506, and Arg679. Objectives To examine which cleavage is most important for inactivation, recombinant factor V molecules were constructed as follows: factor V306Q (R306→Q), factor V506Q (R506→Q), and factor V306Q/506Q (R306→Q and R506→Q). Methods The recombinant molecules were expressed in mammalian cells, purified, and assayed prior and after incubation with APC and lipids for 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The more rapid clearance of FVa 1-506 observed empirically suggests two possible problems with the model construct: 1) the binding affinity between FVa i 506 and FXa is weaker than the model value of 1 nM based on studies with bovine FVa [ 32 ] or 2) APC can cleave at Arg 306 when the FVa i 506 species is bound to FXa. Previous studies with recombinant human proteins have reported K D values ranging from ~3.9 nM [ 31 ] to ~1.35 nM [ 51 ]. To evaluate the likelihood that a weaker binding affinity was the culprit, mathematical simulations were conducted where the K D for the FXaFVa i 506 complex was varied; to fit the empirical data the K D for this complex would have to be greater than 10 nM (data not shown) and as such this adjustment was discarded as a viable option.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The more rapid clearance of FVa 1-506 observed empirically suggests two possible problems with the model construct: 1) the binding affinity between FVa i 506 and FXa is weaker than the model value of 1 nM based on studies with bovine FVa [ 32 ] or 2) APC can cleave at Arg 306 when the FVa i 506 species is bound to FXa. Previous studies with recombinant human proteins have reported K D values ranging from ~3.9 nM [ 31 ] to ~1.35 nM [ 51 ]. To evaluate the likelihood that a weaker binding affinity was the culprit, mathematical simulations were conducted where the K D for the FXaFVa i 506 complex was varied; to fit the empirical data the K D for this complex would have to be greater than 10 nM (data not shown) and as such this adjustment was discarded as a viable option.…”
Section: Resultsmentioning
confidence: 99%
“…To incorporate the formation of the ternary prothrombinase substrate complex, four additional reactions are required (Table 3 , Eqns 19–22). Based on studies indicating that prothrombinase complexes formed with partially proteolyzed FVa species have a K M similar to the complex formed with intact FVa [ 31 , 51 ], we set the K M of prothrombin for any prothrombinase complex to be the same and consistent with previous modeling studies [ 46 , 47 ]. We included two additional reactions (Table 3 , Eqns 23–24) to allow for the dissociation of the ternary complex formed with some of the partially proteolyzed FVa species.…”
Section: Resultsmentioning
confidence: 99%
“…Many mutations have been identified on FV, some of them without any impact on its activities but associated to FV variations in blood concentration 32 , and others with a decreased APC dependent inhibition 21,[33][34][35][36] . The most frequent mutation, which has a unique origin, is the R506Q one, and it is located on one of the APC cleaving sites on FV, at position 506 12,18,19 . FV-L is resistant to the APC-PS cleavage, especially in its activated form, and when bound to phospholipids.…”
Section: Discussion: Fv Mutations and Thrombosis Riskmentioning
confidence: 99%
“…One year later, Bertina's group in Leiden (NL) showed that this defect is the consequence of a FV mutation at position 506, where arginine is replaced by glutamine (noted R506Q), and the mutated factor was named Factor V Leiden (FV-L) 12 . This FV mutation is located on one of the FV cleaving sites by APC 6,[16][17][18][19] . Thrombin activated FV-L has then an increased activity survival time in plasmas from patients with this R506Q mutation, and this can propagate activation of coagulation pathways.…”
Section: Apc-resistance and Factor V-leidenmentioning
confidence: 99%
“…As mentioned above, the main proteolytic process responsible for FVa/FVIIIa regulation is limited proteolysis by the serine protease activated protein C (APC). The inactivation process occurs much in analogy to the activation described before: APC targets its substrates at multiple but specific cleavage sites, provided that both the substrate and the enzyme are bound to a membrane surface (Kalafatis et al, 1994;Nicolaes et al, 1995, Egan et al, 1997, Barhoover & Kalafatis, 2011. In the absence of a lipid surface, reactions occur too slowly to be physiologically relevant (Bakker et al, 1992;Nicolaes et al, 1995).…”
Section: Regulation Of Fva and Fviiia Activitiesmentioning
confidence: 99%